Primary Antiphospholipid Syndrome Associated with Pneumonia: A Case Report of a 16-Year-Old Male Patient. (22nd March 2015) - Yilmaz, Süreyya; Topcu, Fusun; Selimoglu Sen, Hadice; Yildirim, Yasar; Yilmaz, Zülfükar; Kara, Ali Veysel; Akgul Ozmen, Cihan
Abstract : Antiphospholipid syndrome (APS) is an autoimmune disease characterised by arterial and/or venous thrombosis and/or recurrent pregnancy loss in the presence of antiphospholipid (APL) antibodies. It is evaluated as APS when it develops associated with other systemic autoimmune diseases or primary APS if there is no concomitant disorder. In this study, we present a case of a 16-year-old male patient with primary APS. The patient was admitted with presumptive diagnosis of pneumonia, but multiple pulmonary thromboembolism (PTE) was observed on computerized tomography (CT) pulmonary angiography. APL antibodies positivity and thrombocytopenia developed in our patient. The patient was evaluated as primary APS since another etiology that could explain PTE was not found. Primary APS is a rare disease in children along with adolescents, compared with APS associated with other systemic autoimmune diseases. We present here a young male patient with primary APS and PTE to contribute to the literature. The patient initially had pneumonia but later developed PTE and thrombocytopenia.